The Influence of Labor and Raw Material Volume on Tofu Production in Micro-Enterprises in Sidodadi Village - Fadilah, Erika; Dailami, D.; Maya, Indah; Kartika, Noni Rahma; Yolanda, Della Ayu; Sirait, Khoiriza Salsabila; Aprida, Cici Ayu (Manunggal Halim Jaya, 2026)
Micro-enterprises engaged in tofu production in Sidodadi Village, Asahan Regency, play an important role in supporting the local economy. However, these enterprises often encounter challenges in optimizing key production factors, particularly the availability of labor and raw materials. The core issue of this study is to determine how far these two factors influence the level of tofu production. This research aims to analyze the effect of the number of workers and the volume of raw materials on tofu production among micro-enterprises in the region. A quantitative method with multiple linear regression analysis was applied, supported by data collection through observation, interviews, and questionnaires distributed to business actors and workers. The results revealed that both labor and raw materials have a significant partial and simultaneous effect on tofu production volume. The F test confirmed the model’s feasibility (F = 69.238, Sig. = 0.000), while the t test showed that each independent variable significantly affected production (Sig. < 0.05). The Adjusted R² of 0.064 indicates that 6.4% of the variation in tofu production can be explained by the two variables. These findings imply that improving labor efficiency and managing raw material availability are essential strategies for enhancing productivity and strengthening the economic empowerment of micro-enterprises in Sidodadi Village.